Kaner-ki-Putli Temple - Temples of India Project Team (Jio Institute, 2024)
The Kaner-ki-Putli Temple is named after the flower buds of the Kaner or Oleander plant. The temple is dedicated to Shiva. The present structure was in a ruinous state and has been restored by the Archaeological Survey of India with a boundary wall and a pathway guiding visitors to the temple.